(untitled) (Global Journal of Science Frontier Research, 2020)
The use of ethanol has low toxicity, is almost harmless to the human body, and has the characteristics of quickly absorbing the water in viruses and bacteria, causing the protein to dehydrate and freeze, leading to the rapid death of viruses and bacteria; it is directly vaporized with anhydrous ethanol, mixed with air, and modulated An appropriate concentration of therapeutic gas mixture is used to allow patients to inhale the respiratory tract or fasting digestive tract for direct disinfection and sterilization; it is used to treat all respiratory or digestive tract infectious diseases caused by viral and bacterial infections containing protein structures.